Ekstrak Konsentrasi Hambat Minimum (KHM) dan Konsentrasi Bakterisida Minimum (KBM) Daun Henna Kuku NADES Terhadap Bakteri Bacillus Cereus - Eka Nur Septya; Renny Amelia; Ine Suharyani (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: This study aims to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) concentrations of the NADES extract of henna leaves (Lawsonia inermis L.) against Bacillus cereus bacteria. Methods: This research is a descriptive type of research that was conducted at the Phytochemical Laboratory and Microbiology Laboratory of Sekolah Tinggi Farmasi Muhammadiyah Cirebon. Collecting data from the MIC test results by looking at the turbidity at each concentration and the MBC results by looking at the presence or absence of bacterial growth. Results: The MIC sample could not be obtained because it looked cloudy, and bacteria were still growing on the media. In contrast, the MBC sample was only 100%, which could inhibit bacteria's growth on the media. The positive control of Ciprofloxacin at a concentration of 100 mg had a diameter of 2.34 cm, 125 mg had a diameter of 2.39 cm, 150 mg had a diameter of 2.47 cm, and the negative control NADES solution had a diameter of 0.98 cm. Conclusion: The Minimum Inhibitory Concentration (MIC) cannot be known because the results of the NADES extract of henna leaves compared to before and after incubation still look cloudy due to factors from the sample. In the other hand, Minimum Bactericidal Concentration (MBC) can only be known at a concentration of 100%, which can kill the growth of Bacillus cereus bacteria.